Natural Immunity to HIV: A Delicate Balance between Strength and Control - Poudrier, Johanne (Hindawi Publishing Corporation, 2012)
Understanding how the mucosal immune system in the human female reproductive tract might prevent or facilitate HIV infection has important implications for the design of effective interventions. We and others have established cohorts of highly-exposed, HIV-seronegative individuals, such as HIV-uninfected commercial sex workers, who have remained HIV-negative after more than 5 years of active prostitution. Observations obtained in studies of such individuals, who represent a model of natural immunity to HIV, indicate that HIV resistance may be associated with the host's capacity to preserve systemic integrity by constraining immune activity and controlling inflammatory conditions at the mucosal point of entry. This likely necessitates the orchestration of balanced, first-line and adaptive immune responses.